Hydration of 3-hydroxy-4, 4-dimethylglutaric acid with dimethylamine complex and its atmospheric implications. Issue 40 (4th October 2018) - Han, Ya-Juan; Feng, Ya-Juan; Miao, Shou-Kui; Jiang, Shuai; Liu, Yi-Rong; Wang, Chun-Yu; Chen, Jiao; Wang, Zhong-Quan; Huang, Teng; Li, Jie; Huang, Wei
Abstract : Changes in temperature affects the distribution of isomers, which facilitates the understanding of new particle formation in the atmosphere. Abstract : Atmospheric aerosols have a tremendous influence on visibility, climate, and human health. New particle formation (NPF) is a crucial source of atmospheric aerosols. At present, certain field observations and experiments have discovered the presence of 3-hydroxy-4, 4-dimethylglutaric acid (HDMGA), which may participate in NPF events. However, the nucleation mechanism of HDMGA has not been clearly understood. In addition, dimethylamine (DMA) is an important precursor of nucleation. The nucleation mechanism involving HDMGA and DMA has not been studied. In this study, the most stable structures of (HDMGA)(H2 O) n ( n = 0–3) and (HDMGA)(DMA)(H2 O) n ( n = 0–3) were obtained by using M06-2X coupled with the 6-311++G(3df, 3pd) basis set. The α-carboxyl group is directly attached to the amino group in all the most stable configurations. Proton transfer enhances the strength of a hydrogen bond, as well as promotes the generation of a global minimum structure. Temperature has a considerable influence on the distribution of isomers for (HDMGA)(DMA)(H2 O)3 as compared to the other investigated clusters. The Gibbs free energy values reveal that most of the clusters can exist in NPF, except for (HDMGA)(H2 O)1 . The process of adding a cluster of (H2 O) n more likely occurs in the atmosphere than gradually adding a single water molecule.